Apparent Diffusion Coefficient Values of Middle Ear Cholesteatoma Differ from Abscess and Cholesteatoma Admixed Infection - Thiriat, S.; Riehm, S.; Kremer, S.; Martin, E.; Veillon, F. (American Journal of Neuroradiology, 2009)
SUMMARY: A retrospective study was conducted on a cohort of 15 patients who underwent surgery because cholesteatoma or abscess was suspected. All patients had MR imaging prior to surgery with diffusion-weighted images (DWI) from which the apparent diffusion coefficient (ADC) value was calculated. Using this technique, we were able to determine 3 distinct ADC value ranges corresponding to the 3 groups of lesions found at surgery (pure cholesteatoma, cholesteatoma with infection, and abscess or infection). This needs to be confirmed by further studies with a wider range of patients.